The role of probiotics in the prevention and management of cardiovascular diseases: insights from a doxorubicin-induced model. - Starovoitova, Svitlana; Palamarchuk, Andriy (My University, 2025)
Probiotics, postbiotics and gut microbiota can influence in pain modulation, including: visceral pain, inflammatory pain, postoperative pain, neuropathic pain, osteoarthritis pain, musculoskeletal pain, complex regional pain syndrome, fibromyalgia. Probiotics can increase the expression of cannabinoid and opioid receptors in colonic epithelial cells, which mediate analgesia and reduce hypersensitivity to pain stimuli. They modulate key immune signaling pathways and cytokine production. This immunomodulation leads to decreased pro-inflammatory cytokines and increased anti-inflammatory cytokines, reducing inflammation-induced pain. By improving intestinal barrier function (e.g., enhancing tight junction proteins and mucin production) and competitively excluding pathogens, probiotics reduce gut permeability and inflammation, which can influence visceral pain perception. Certain probiotic strains produce neurotransmitters like serotonin, -aminobutyric acid, and dopamine, which affect gut motility, mood, and pain signaling via the gut-brain axis. Bacterial proteases from probiotics can activate or inhibit protease-activated receptors on nerve terminals and epithelial cells, modulating nociceptor excitability and visceral pain. In osteoarthritis pain models, probiotics reduce expression of pain mediators in dorsal root ganglia and joint tissues, while increasing protective molecules like type II collagen and tissue inhibitor matrix metalloproteinase 1. Also, the gut microbiota plays a significant role in the pathophysiology of fibromyalgia syndrome, potentially influencing pain, mood, and sleep through the gut-brain axis. Postbiotics ameliorate bone loss in estrogen-deficient animal models by improving bone mineral content in the spine and femur, suggesting potential benefits for bone health and indirect relief of musculoskeletal pain. Research underscores the potential of probiotics as innovative analgesics with fewer side effects than conventional drugs, acting on pain-related receptors.Cardiovascular diseases (CVDs), particularly acute myocardial infarction, represent a critical global health concern driven by multifactorial risk factors, including hypercholesterolemia. While conventional lipid-lowering therapies remain effective, their side effects and limitations have prompted the exploration of alternative approaches. Probiotics, postbiotics, and functional foods have emerged as innovative strategies capable of modulating the gut microbiota to enhance lipid metabolism and mitigate oxidative stress and inflammation, offering new possibilities for CVD management. This review emphasizes the significance of doxorubicin-induced models in studying CVD mechanisms and evaluating therapeutic potentials. By leveraging insights into the gut-microbiota-heart axis, these models facilitate the development of novel interventions targeting hypercholesterolemia-induced CVDs. Cholesterol-lowering probiotic strains and functional food products stand out for their ability to provide safer, complementary options to traditional therapies. Advancing research in this field requires optimizing experimental models, investigating molecular pathways, and translating findings into clinical practice through rigorous trials. The integration of these innovative solutions holds the potential to improve cardiovascular health, address unmet clinical needs, and reduce the global burden of CVDs. Серцево-судинні захворювання (ССЗ), зокрема гострий інфаркт міокарда, є критичною глобальною проблемою охорони здоров'я, обумовленою багатофакторними ризиками, включаючи гіперхолестеринемію. Хоча традиційні методи зниження рівня ліпідів залишаються ефективними, їх побічні ефекти та обмеження стимулювали пошук альтернативних підходів. Пробіотики, постбіотики та функціональні продукти харчування стали інноваційними стратегіями, які здатні модулювати мікробіоту кишечника, покращувати ліпідний обмін та зменшувати оксидативний стрес і запалення, відкриваючи нові можливості для управління ССЗ. У цьому огляді підкреслюється значущість моделей, індукованих доксорубіцином, для вивчення механізмів ССЗ та оцінки терапевтичного потенціалу. Завдяки використанню знань про вісь кишечник-мікробіота-серце ці моделі сприяють розробці нових інтервенцій, спрямованих на ССЗ, викликані гіперхолестеринемією. Пробіотичні штами, що знижують рівень холестерину, та функціональні харчові продукти вирізняються своєю здатністю забезпечувати більш безпечні та доповнюючі варіанти до традиційних терапій. Подальший розвиток досліджень у цій галузі вимагає оптимізації експериментальних моделей, вивчення молекулярних шляхів та переведення отриманих результатів у клінічну практику через ретельні випробування. Інтеграція цих інноваційних рішень має потенціал для покращення серцево-судинного здоров’я, задоволення невирішених клінічних потреб та зниження глобального тягаря ССЗ.
Keywords: кафедра біотехнології і мікробіології; probiotic; postbiotic; gut microbiota; functional foods; cholesterol metabolism; постбіотик; функціональні продукти харчування; мікробіота кишечника; метаболізм холестерину; метаболізм холестерину; доксорубіцин-індуковані моделі